Navigating paved paradise: Evaluating landscape permeability to movement for large mammals in two conservation priority landscapes in India. (July 2020) - Jayadevan, Anisha; Nayak, Rajat; Karanth, Krithi K.; Krishnaswamy, Jagdish; DeFries, Ruth; Karanth, K. Ullas; Vaidyanathan, Srinivas
Abstract: Human land use and activity results in the loss of habitat and biodiversity, and alters how animals move through landscapes. Spatially explicit information on where animal movement is affected at large spatial scales is crucial for prioritizing conservation efforts. We evaluated landscape permeability to movement in two conservation priority landscapes in India, the Western Ghats (WG) and Central India (CI). Using an agent-based model we simulated movement and dispersal of five wide-ranging species in WG (elephant, gaur, leopard, sambar and sloth bear) and four in CI (gaur, leopard, sambar and sloth bear). For each species we compared movement in the presence and absence of land-use land-cover, infrastructure and human population to identify areas where movement is impeded and reduced due to high-resistance features; unrestricted due to relatively low-resistance features; and increased and channelled due to surrounding high-resistance areas. In both landscapes, median movement was reduced. Human land-use, human population and high linear infrastructure density contribute the highest to impeded movement for all species. Natural areas constitute only 20–55% and 50–70% of unrestricted, increased and channelled movement areas in WG and CI respectively. This suggests that a large percentage of the landscape crucial for maintaining movement is not completely permeable. Such areas are often neglected in conservation planning. Our spatially explicit results help identify and prioritize areas where restoration or mitigation should be planned to improve permeability to movement for large mammals. Our approach can be used for other landscapes where data on large mammal movement is lacking. Highlights: Median permeability to movement for all species in both landscapes was reduced. Reduced movement is due to human land-use, human population and linear infrastructure. Natural areas occupy only 20–55% of high permeability areas in WG and 50–70% in CI. Thus permeability is not complete in areas crucial for movement. Our spatially explicit results help prioritize restoration and mitigation measures.